(untitled) (CIPEEX, 2025)
This study investigates the balance between public security and the preservation of individual freedoms in the context of home searches carried out by police authorities in Brazil. Using a qualitative approach and deductive method, the work analyzes legislation, doctrines and jurisprudence to understand how home searches are justified and carried out, emphasizing the need for a rigorous application of the principles of legality, proportionality and necessity. The research results highlight a tension between the need to protect society and respect for individual rights, highlighting the conditions under which authorities can intervene in the private sphere of citizens. The study understands that home searches are essential for public safety, but the execution of these operations requires well-founded justifications to avoid abuses and violations of fundamental rights. As a result of this research, it was realized that the decisions of higher courts, despite providing clear guidelines, are often applied inconsistently, resulting in practices that can compromise public trust in security institutions. Therefore, it is essential that police forces are adequately instructed on the limits of their actions and that there is effective supervision to ensure that interventions are both justified and necessary, strengthening the legitimacy of police operations and the protection of civil rights.